Cultural Encounters and Emergent Practices in Conflict Resolution Capacity-Building (Rethinking Peace and Conflict Studies, 2018)
While waves of scholarship have focused either on the value of presumed universal models or of traditional practices of conflict resolution, curiously missing has been the recognition and analysis of the actual intermingling and interacting of western and local cultural practices that have produced new and emergent practices in our global community. In this compilation of case studies, the authors describe partnerships forged between local practice expertise and bearers of "western/institutional" models to build innovative approaches to mediation and conflict resolution. Including stories of these experiences and the resulting hybrid models that emerged, the book explores central questions of cultural variation and integration, such as the perception of purpose and function of resolution processes, attitudes toward conflict, arenas and timeframes, third party roles, barriers to process use, as well as how to remain true to culture and context. It also examines partnership dynamics and lessons learned for modern cross-cultural collaboration. Tamra Pearson d'Estrée co-directs the interdisciplinary Conflict Resolution Institute at the University of Denver, USA, and is the Henry R. Luce Professor of Conflict Resolution in the Josef Korbel School of International Studies. Her research areas include identity dimensions of social and ethnic conflict, intergroup conciliation and reconciliation, procedural justice, and evaluation frameworks for conflict resolution. She is also involved in conflict resolution training and capacity-building, and facilitates intergroup interactive problem-solving workshops. Ruth J. Parsons is Research Professor at the Conflict Resolution Institute, Joseph Korbel School of International Studies, University of Denver, USA. She has taught, consulted on curriculum development, trained and conducted research in conflict resolution for 30 years. Her specific area of research and writing include culturally based perspectives, strategies and methods for conflict resolution and peacebuilding, as well as social work practice and empowerment.